The feasts of Israel seasons of the Messiah - Scott, Bruce (Bellemawr, NJ The Friends of Israel Gospel Ministry, 1997)
Includes bibliographical references and illustrations.
Keywords: Judaism -- Holy days; Messiah -- typology